Pengembangan Aplikasi Web Reservasi Paket Wisata menggunakan MERN Stack (Studi Kasus: Zona Tamasya Tour Organizer) - Rezki Triandy; Nurudin Santoso (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Zona Tamasya as one of the travel agency provides a variety of tour services. The most popular and best seller service is the open trip tour package. Customers who want to take an open trip can book or reserve a place in advance by contacting Zona Tamasya (admin) via the Whatsapp application. When there is an increase in the number of customers, especially during the holiday season, the admin of Zona Tamasya is quite overwhelmed to respond to any messages that come from customers, both from customers who only ask for information to confirm payment. This weakness makes Zona Tamasya plan to improve the quality of its services by utilizing the website as a medium of information and transactions (reservations). In this research, a web-based application was developed that can be used to make travel package reservations. This application was developed using MERN stack technology (MongoDB, Express, React, and Node.js) and integrates online payment systems. Development is carried out following the principles of software engineering in a linear fashion. The results of the study are web-based applications with the main features of package tours and online payment that have been tested for their functionality.